T2 Hypointensity Aids in the Diagnosis of Intracranial Metastatic Adenocarcinoma. (March 2020) - Faiz, Khunsa; Botsford, Alex; Sinha, Namita; Walling, Simon; Shankar, Jai Jai Shiva
ABSTRACT: Background: The T2 hypointensity has been suggested to be associated with intracranial metastatic adenocarcinomas (IMA). The purpose of our study was to determine the association of T2 hypointensity with IMA. Methods: All patients with pathologically confirmed metastatic brain tumors who had a magnetic resonance imaging (MRI) at our institution in the last 10 years were retrospectively assessed. Qualitative assessment of the lesions on MRI was done by two separate readers who were blinded to the pathological diagnosis. For qualitative assessment, the T2 hypointensity in the lesion was compared with the contralateral normal appearing white matter. Odds ratio, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: Of 107 patients with intracranial metastasis, only 73 (40 females; 33 males; mean age 61 years) had MRI available for review. Of these, only 46 (25 females; 21 males; mean age 61 years) had pathologically proven IMA. T2 hypointensity was seen in 20% of IMA. The odds ratio of T2 hypointensity in IMA was 3 compared to nonadenocarcinomas but was not statistically significant (p = 0.16). Intralesional hemorrhage was seen in 20. When controlled for hemorrhage, the odds ratio for T2 hypointensity in IMA was 4.7. The specificity, sensitivity, PPV, and NPV for T2 hypointensity to diagnose IMA were 92%, 19%, 81%, and 40%, respectively. Conclusion: T2 hypointensity was seen only in 20% of IMA with an odds ratio of 4.7. T2 hypointensity showed a high specificity and PPV for diagnosis of IMA.